2019
DOI: 10.1111/jfbc.12973
|View full text |Cite
|
Sign up to set email alerts
|

Protective activity of mogroside V against ovalbumin‐induced experimental allergic asthma in Kunming mice

Abstract: We investigated the antiasthmatic effect of mogroside V (Mog V) in mice with ovalbumin (OVA)‐induced asthma. Administration of Mog V effectively attenuated OVA‐induced airway hyperresponsiveness and reduced the number of inflammatory cells in bronchoalveolar lavage fluid (BALF). Histological examination showed that Mog V reduced the inflammatory infiltration of the lungs in the asthmatic mice. ELISAs suggested that Mog V effectively decreased the levels of IL‐4, IL‐5, and IL‐13 in BALF and serum levels of OVA‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…After Rbs administration, the inflammatory macrophages and eosinophils in the BALF of mice with asthma were notably reduced. In our previous study, we also observed that the inflammatory cells (i.e., lymphocytes macrophages and eosinophils) were decreased by Mogroside V (a triterpene glucoside) in the BALF of asthmatic mice (Song et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…After Rbs administration, the inflammatory macrophages and eosinophils in the BALF of mice with asthma were notably reduced. In our previous study, we also observed that the inflammatory cells (i.e., lymphocytes macrophages and eosinophils) were decreased by Mogroside V (a triterpene glucoside) in the BALF of asthmatic mice (Song et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…Thirty‐five mice were stochastically divided into the group of normal mice, group of OVA mice, or groups of OVA plus Rbs mice at 50, 150, or 300 mg Rbs/kg body weight ( n = 7 mice/group). Experimental asthma was induced in the mice using a previously described method (Song et al, 2019). The mice were sensitized by intraperitoneal injection of inducing reagents on Day 1 and Day 14.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of mogroside V lowered the levels of different interleukin viz. IL-4, IL-5 and IL-13 in broncho alveolar lavage fluid (BALF) plus serum levels of ovalbumin (OVA)-induced inflammation in the asthmatic mice (Song et al, 2019). Mogrosides exhibited anti-inflammation properties in murine macrophage RAW 264.7 cells by down regulation of certain inflammatory genes such as iNOS, cyclooxygenase-2 COX-2 and interleukins (ILs) and upregulation of protective genes TRP53, PARP1, MAPK9 and BCL2l1.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…According to historical records, the fructus of Siraitia grosvenorii has several effects, such as profit lung, laxative, clear heat, and treatment of sore throat [ 18 ]. Moreover, according to numerous studies, Mogrosides also display multiple pharmacological effects on cancer, oxidative stress, inflammation, obesity, and diabetes [ 18 20 ]. Mog is one of the most effective components of Mogrosides.…”
Section: Introductionmentioning
confidence: 99%